2005
DOI: 10.1128/aem.71.11.6863-6869.2005
|View full text |Cite
|
Sign up to set email alerts
|

Common, but Complex, Mode of Resistance of Plutella xylostella to Bacillus thuringiensis Toxins Cry1Ab and Cry1Ac

Abstract: A field collected population of Plutella xylostella (SERD4) was selected in the laboratory with Bacillus thuringiensis endotoxins Cry1Ac (Cry1Ac-SEL) and Cry1Ab (Cry1Ab-SEL). Both subpopulations showed similar phenotypes: high resistance to the Cry1A toxins and little cross-resistance to Cry1Ca or Cry1D. A previous analysis of the Cry1Ac-SEL showed incompletely dominant resistance to Cry1Ac with more than one factor, at least one of which was sex influenced. In the present study reciprocal mass crosses between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0
3

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 54 publications
(44 citation statements)
references
References 41 publications
0
41
0
3
Order By: Relevance
“…Cry1Ac protoxins were produced as inclusion bodies in E. coli cultures and purified as previously described (30). Cry1Ac crystals were diluted in sterile distilled water and incorporated into sterile diet at five concentrations as described previously by Gilliland et al (12).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cry1Ac protoxins were produced as inclusion bodies in E. coli cultures and purified as previously described (30). Cry1Ac crystals were diluted in sterile distilled water and incorporated into sterile diet at five concentrations as described previously by Gilliland et al (12).…”
Section: Methodsmentioning
confidence: 99%
“…Fifty percent lethal concentration (LC 50 ) or 50% lethal dose (LD 50 ) estimates and their 95% fiducial limits (FLs) were calculated by logit regression using GLIM 3.77 (1985; Numerial Algorithms Group) as previously described (30)…”
mentioning
confidence: 99%
“…Although this finding was consistent with a defect in toxin activation the authors noted that alternative explanations existed -such as preferential sequestration of the protoxin form. In a related paper a resistant population was once again found to be more susceptible to activated toxin, although no defect in toxin activation could actually be established [10]. Another example where an indirect observation could have had several explanations was seen in a paper by Sayyed et al [11] in which it was observed that an esterase inhibitor could synergise the activity of a Cry toxin against a resistant population.…”
Section: Alternative Resistance Mechanisms and The Casual Vs Causal Pmentioning
confidence: 95%
“…One such paper [10] suggests that resistance was inherited in an incompletely dominant fashion and showed some maternal influence. These differences may represent multiple mutations/mechanisms of resistance but may also reflect significant differences in genetic backgrounds that can confound the analysis of the major resistance-causing mutation(s).…”
Section: How Many Mutations Cause Resistance In Plutella?mentioning
confidence: 99%
“…Other populations resistant to Cry toxins have also been shown to exhibit polygenic resistance: for example, populations of H. virescens (46) and H. armigera (47) resistant to Cry2A and populations of P. xylostella (32) and P. gossypiella (48) resistant to Cry1Ac. Nevertheless, monogenic resistance has been found in other populations of H. virescens (37), H. armigera (41), P. xylostella (49), and Ostrinia nubilalis (50).…”
Section: Discussionmentioning
confidence: 99%